(untitled) (Scientific journal of the Fergana State University, 2024)
We know that the quality of the soil, that is, its chemical composition, directly affects the growth, development, productivity of medicinal plants, as well as the quality of the drugs made from them, since the soil provides medicinal plants with the necessary nutrients. This, in turn, depends on the type of plant and its biological characteristics. In this regard, today, not only the study of biologically active substances included in the soil or medicinal plants, but also the study of chemical elements exposed to environmental factors is of great scientific and practical importance. In addition, we set the task of determining the coefficient of biological absorption of lavender thin-leaved (Lavandula angustifolia Mill.) from the point of view of assessing the environmental purity of medicinal plants, which requires special attention to the issue of environmental monitoring of the amount of heavy metals and the development of sanitary maximum permissible concentration in medicinal plants.